The effects in humans of rapid loss of body mass on a boxing-related task - Smith, M. S.; Dyson, R.; Hale, T.; Harrison, J. H.; McManus, P. (European Journal of Applied Physiology, 2000)
The physiological effects of strategies for a rapid loss of body mass immediately before weighing-in for competition in weight-governed sports are unclear. This study examined the effects of a 3%-4% loss in body mass on a boxing-related task. Seven novice amateur boxers completed three 3 min rounds of simulated boxing on a prototype boxing ergometer in an euhydrated state (E-trial) and after exercise-induced thermal dehydration (D-trial). All subjects lost body mass following dehydration-mean body mass fell 3.8 (SD ± 0.3)% [77.3 (SD ± 11.3) to 74.4 (SD ± 10.7) kg, P < 0.001] - but changes in plasma volume (PV) were inconsistent. Four subjects suffered reductions in PV between 15% and 30%, one subject maintained his E-trial value and two recorded an increase. The D-trial mean PV value was 8.0 (SD ± 17.2)% lower but this fall was not statistically significant (P > 0.05). Analysis of D-trial boxing performance showed one subject maintained his performance over the two trials and a second improved 17.8%. A two-way ANOVA (condition × time) with repeated measures on both factors showed no significant main effect differences for condition (F1,6=3.93 P > 0.05), time (F1.83,48=1.12, P > 0.05) or interaction between them (F1.93,48, P > 0.05). Furthermore, neither heart rate nor blood lactate responses in the boxing task differed between trials. These data were affected by the small sample. Power and effect size analysis using <eta>2 procedure and removing the outlier data produced a mean fall in boxing performance of 26.8%. However, some subjects appeared able to resist the deleterious effects of a rapid loss of body mass prior to competition and further research is needed to explain the mechanisms under-pinning this ability.